The effect of cross-training on the development of some physical abilities on the performance level of some basic volleyball skills Experimental research on a sample of Soran volleyball club juniors (Journal of the College of Basic Education, 2023)
Summary of the research:The game of volleyball is characterized by a high level of performance and competition, as it provides elements of excitement, suspense, and pleasure for those who deal with it at all levels, and this is what made it among the group Olympic games that are popular in the world. The necessity of having special physical capabilities that qualify the player for the quality of skillful performance, which reflects the importance of designing standardized training programs that aim to improve the components of the player’s training status by following the scientific method in light of the development witnessed in the sports field. The aim of the research is to identify the effect of cross-training on the development of some physical abilities of volleyball juniors. And to identify the impact of the development of some physical abilities on the level of performance of some of the basic skills of the volleyball juniors, the experimental approach with an experimental design was used for one experimental group with the application of the pre and post measurement systems, where the research sample community was chosen by the intentional method with a total number of (30) juniors Among the players of the volleyball teams is Soran Club in the Kurdistan Region of Iraq. The training program was applied to a sample of (12) regular youth in training within the volleyball team for the 2010/2011 season. And after taking the statistics of the primary variables of the research sample, it was proven that the sample was free from defects in non-moderate distributions, which may reflect the homogeneity of the research sample in the primary variables. Then the researcher conducted the pre-tests and then applied the training program after it was developed according to the appropriate scientific foundations for the research and the sample. Then the post-tests. In order to process the raw scores of the results of the tests, the researcher used a set of statistical equations to reach the final results, to show that the training program using cross-training applied - under study - had a positive impact on the development of the level of physical abilities of the volleyball junior, in addition to the development of the level of physical abilities Using cross-training applied - under study - has had a positive impact on the level of performance of some basic skills of volleyball juniors. In conclusion, the researcher recommended a set of recommendations, including following the scientific foundations for planning the preparation period and rationing the training loads in the training programs to raise the level of the components of the training situation in general, and the physical and skill in particular.Keywords: cross training, physical abilities, basic skills in volleyballThe Plane